THE EFFECT OF PROFITABILITY (ROA AND ROE) ON THE STOCK PRICES OF DIGITAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE 2021-2024 PERIOD - Siti Nurindah Hasan; Siti Pratiwi Husain; Yustina Hiola (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of profitability, proxied by Return on Assets (ROA) and Return on Equity (ROE), on stock prices of digital banks listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. This study employed a quantitative approach with multiple linear regression analysis processed using SPSS. The sample consisted of seven companies using quarterly data. The sampling technique used was saturated sampling. The results indicate that Return on Assets (ROA) and Return on Equity (ROE) influence stock prices, but are not statistically significant. Simultaneously, ROA and ROE also influence stock prices, but are insignificant. These findings indicate that profitability is not yet a primary factor influencing digital bank stock prices, suggesting that other factors beyond the research variables play a more significant role in determining stock price movements.